2000
DOI: 10.1515/jpem.2000.13.s1.687
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Central Precocious Puberty in Males: The Results of the Italian Study Group for Physiopathology of Puberty

Abstract: We reviewed the hospital records of 45 boys, followed in 13 pediatric departments throughout Italy, who had undergone computed tomography and/or magnetic resonance imaging for central precocious puberty (CPP). Twenty-seven patients (60%) had idiopathic CPP and 18 (40%) neurogenic CPP. A hamartoma of the tuber cinereum was found in six patients (33%). All patients with hypothalamic hamartoma had earlier onset of symptoms than patients with idiopathic CPP. Five patients (27%) were affected by type 1 neurofibroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 9 publications
6
38
0
8
Order By: Relevance
“…Similar to the present study, Rizzo et al [3] found that an underlying organic cause was present in 25% of the cases; however, while Rizzo et al [3] evaluated only 12 male CPP cases, in the present study, 100 male cases were evaluated, which makes this study one of the most comprehensive studies with respect to the number of cases. The study by De Sanctis et al [15], which included 45 cases, found that the incidence of organic cases was 40%, while this rate is 48.7% in the review by Pigneur et al [16]. In our study, MRI showed that 77% of the cases with an organic pathology had space-occupying lesions, while 23% of the cases had developmental anomalies of CNS.…”
Section: Discussionsupporting
confidence: 45%
“…Similar to the present study, Rizzo et al [3] found that an underlying organic cause was present in 25% of the cases; however, while Rizzo et al [3] evaluated only 12 male CPP cases, in the present study, 100 male cases were evaluated, which makes this study one of the most comprehensive studies with respect to the number of cases. The study by De Sanctis et al [15], which included 45 cases, found that the incidence of organic cases was 40%, while this rate is 48.7% in the review by Pigneur et al [16]. In our study, MRI showed that 77% of the cases with an organic pathology had space-occupying lesions, while 23% of the cases had developmental anomalies of CNS.…”
Section: Discussionsupporting
confidence: 45%
“…The pathological CNS lesions responsible for CPP and PPP in our study were similar to those in previous studies20-23) (Table 4). The underlying disease of the youngest boy presenting with CPP in our study was a hypothalamic hamartoma, which was reported previously in a 7-month-old infant with PP24).…”
Section: Discussionsupporting
confidence: 90%
“…Hypothalamic hamartomas are responsible for CPP in 2-28% of patients [29,31]. These are congenital, non-neoplastic tumor-like lesions formed by heterotopic grey matter, neurons, glial cells and fiber bundles located at the base of the brain at the floor of the third ventricle, near to the tuber cinereum or to the mamillary bodies [32][33][34][35].…”
Section: Normal Pubertymentioning
confidence: 99%